Mex-Cine : Mexican filmmaking, production, and consumption in the twenty-first century - Aldama, Frederick Luis, 1969- (The University of Michigan Press, 2013)
"Mex-Cine; offers an accessibly written, multidisciplinary investigation of contemporary Mexican cinema that combines industrial, technical, and sociopolitical analysis with analyses of modes of reception through cognitive theory. Mex-Cine; aims to make visible the 21st-century Mexican film industry, its blueprints, and the cognitive and emotive faculties involved in making and consuming its corpus. A sustained, free-flowing book-length conversation between two leading scholars, Mex-Cine; enriches our understanding of the way contemporary Mexican directors use specific technical devices, structures, and characterizations in making films in ways that guide the perceptual, emotive, and cognitive faculties of their ideal audiences, while providing the historical contexts in which these films are made and consumed"--